"Violencia, tecnocratismo y vida cotidiana", de Rafael Ángel Herra - Aguilera, Gabriel (Universidad de Costa Rica, 2006)
Reseña del libro "Violencia, tecnocratismo y vida cotidiana", de Rafael Ángel Herra.